Exploring Excitotoxicity and Regulation of a Constitutively Active TRP Ca2+ Channel in Drosophila - Bih-Hwa Shieh; Lucinda Nuzum; Inga Kristaponyte (Fly, 2021)
Unregulated Ca2+ influx affects intracellular Ca2+ homoeostasis, which may lead to neuronal death. In Drosophila, following the activation of rhodopsin the TRP Ca2+ channel is open to mediate the light-dependent depolarization. A constitutively active TRP channel triggers the degeneration of TrpP365/+ photoreceptors. To explore retinal degeneration, we employed a multidisciplinary approach including live imaging using GFP tagged actin and arrestin 2. Importantly, we demonstrate that the major rhodopsin (Rh1) was greatly reduced before the onset of rhabdomere degeneration; a great reduction of Rh1 affects the maintenance of rhabdomere leading to degeneration of photoreceptors. TrpP365/+ also led to the up-regulation of CaMKII, which is beneficial as suppression of CaMKII accelerated retinal degeneration. We explored the regulation of TRP by investigating the genetic interaction between TrpP365/+ and mutants affecting the turnover of diacylglycerol (DAG). We show a loss of phospholipase C in norpAP24 exhibited a great reduction of the DAG content delayed degeneration of TrpP365/+ photoreceptors. In contrast, knockdown or mutations in DAG lipase (InaE) that is accompanied by slightly reduced levels of most DAG but an increased level of DAG 34:1, exacerbated retinal degeneration of TrpP365/+. Together, our findings support the notion that DAG plays a role in regulating TRP. Interestingly, DAG lipase is likely required during photoreceptor development as TrpP365/+; inaEN125 double mutants contained severely degenerated rhabdomeres.